2011
DOI: 10.1016/j.jpor.2010.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Chewing-induced regional brain activity in edentulous patients who received mandibular implant-supported overdentures: A preliminary report

Abstract: Despite the limitation of a small sample size, these results suggest that the gum-chewing task in elderly edentulous patients resulted in differential neural activity in the frontal pole within the prefrontal cortex between the 2 prosthodontic therapies-mandibular CD and IOD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 23 publications
4
62
0
Order By: Relevance
“…Similar results were found in studies of human chewing that used positron emission tomography (PET) (Momose et al, 1997). These and only a few other neuroimaging studies have provided some understanding of human brain activity related to oral function (Bracco et al, 2010;Kimoto et al, 2011) and parafunction (Tamura et al, 2003;Byrd et al, 2009;Jiang et al, 2010).…”
Section: Introduction Msupporting
confidence: 66%
“…Similar results were found in studies of human chewing that used positron emission tomography (PET) (Momose et al, 1997). These and only a few other neuroimaging studies have provided some understanding of human brain activity related to oral function (Bracco et al, 2010;Kimoto et al, 2011) and parafunction (Tamura et al, 2003;Byrd et al, 2009;Jiang et al, 2010).…”
Section: Introduction Msupporting
confidence: 66%
“…A critical issue in geriatric oral healthcare is the evaluation of individual variations in adapting to dental prostheses. Animal research has confirmed that occlusal changes can induce neuroplasticity in the motor cortex, and fMRI studies have consistently shown that functional changes in the sensorimotor cortex reflect not just individual differences but also continuous adaptation over time . It should be noted, however, that most of the studies included in the current meta‐analysis were observational and cross‐sectional studies, the results of which cannot be interpreted as effects of the neuroplasticity of oral sensorimotor rehabilitation .…”
Section: Discussionmentioning
confidence: 85%
“…Another study reported an increase in prefrontal activation, occlusal force, masticatory muscle activity, in people with dentures and young, healthy controls (natural dentate) as compared to people with tooth loss . Similarly, a few other studies, within the limitation of relatively small sample size, have applied the fMRI technique to show different activation patterns of SI with different dental prosthesis . These findings allow several speculations regarding the evaluation of brain activity and functional rehabilitation.…”
Section: Neuroplasticity In Dental Prosthetic Patientsmentioning
confidence: 90%